Pipelle versus MVA cannula for endometrial biopsy: a comparative study - Garg, Aakriti; Mukherjee, Shobha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Endometrial biopsy procedure is a prerequisite for evaluation of abnormal uterine bleeding, also performed to exclude the presence of endometrial carcinoma or in cases of infertility. Methods: A study was conducted at Rohilkhand Medical College and Hospital, Bareilly among 350 subjects to assess the efficacy and problems associated with endometrial biopsy technique by MVA cannula method and pipelle method of biopsy. Results: Mean age recorded was 45.14±10.11, mean parity was 3.18±1.8, mean endometrial thickness was 6.9±3.28 and mean BMI was 24.3±2.12. In our study, duration of MVA endometrial biopsy was (3.1±0.62min) and with Pipelle method was (3.01±0.77 min). Endometrial biopsy is a compulsory requirement for evaluation of endometrial causes of abnormal uterine bleeding especially malignancy, hence, it is a very frequently done procedure. Conclusions: This study concluded that manual vaccum aspiration using cannula No.4, an unconventional technique was comparable to Pipelle technique with comparable efficacy and results.